A study on the relation of the severity of diabetic foot ulcers with the type of bacterial flora isolated from the wounds - Pal, Bikramjit; Gupta, Sumit Kumar (International Surgery Journal, 2016)
Background: The study is to determine the relation between severity of the diabetic foot ulcers and the organisms isolated from the wounds; its implications and prognosis with particular reference to the differences in the final outcome depending upon the type of organism infecting the wound. The study try to correlate the severity of the diabetic foot infection according to Meggit-Wagner classification, the incidence of amputation and the impact on the hospital stay with the difference of bacterial flora isolated from the wounds. This is an observational study done in 53 patients who were admitted in the surgical ward of a large private medical college in Jadavpur, India. It has been found from this study that the incidence and severity of diabetic foot ulcer is more in patients with some particular type of bacteria found in their wounds. A strong correlation is found in patients whose wounds were infected with some particular bacteria had resulted in more severe type of foot ulcers with higher incidence of amputation and concomitant longer hospital stay. Methods: An observational study was done in 53 patients who were admitted in the surgical ward of a teaching hospital in Kolkata, India. The youngest patient was aged 28 years and the oldest patient was 83 years of age. All of them presented with clinically infected foot ulcers. The patients were explained about the study methods in their own language and due consent was taken. A standardized proforma in English, Hindi and the vernacular languages was made for recording the necessary data. The standard X-ray plates were taken into consideration for determination of the involvement of underlying bones. The microbiological studies were done in all patients from the wound swabs of the foot ulcers. The outcome of the diabetic foot ulcer was assessed from the severity of the disease, the presence of the different bacterial flora in their wounds, the incidence of amputation and the duration of hospital stay. Results: The positive wound culture was found in 67.92 of patients, Methicillin resistant Staph. aureus (MRSA) was the commonest isolated organism (44.44%) followed by mixed bacterial flora (Staph. aureus, Streptococcus epidermidis, Peptococcus, and Bacteroides fragilis) in 16.98% of patients. ESBL Klebsiella was found in 13.89% of patients, Pseudomonas aeruginosa and Enterococcus feacalis were isolated in 8.33% of patients. 80% of ESBL infected wounds presented with Grade IV ulcers. The incidence of amputation was highest in patients whose wounds were colonized by MRSA and 60% of patients with ESBL Klebsiella infected wounds had hospital stay of more than three weeks. Conclusions: The study observed that the prognosis and outcome of a diabetic foot ulcer vary considerably with the specific type of bacteria colonizing the wound.